Salaf-Khalaf Education Integration Model as an Adaptation Strategy for the Roudlotul Mubtadiin Islamic Boarding School in the Society 5.0 Era - Risalatul Aliyah; Ahmad Saefudin (Mauriduna : Journal of Islamic Studies, 2025)
Islamic boarding school education today faces the challenge of balancing the traditional salaf approach, which emphasizes mastery of classical religious texts, with the khalaf approach, which focuses on formal education, modern knowledge, and digital skills. This study aimed to analyze the implementation of the integration of these two educational models at Pondok Pesantren Roudlotul Mubtadiin Balekambang and to evaluate its relevance in the Society 5.0 era. This research employed a descriptive qualitative approach, using in-depth interviews, participatory observation, and documentation, which it involved the pesantren's caretaker, head of the madrasah, teachers, daily administrators, and students from various educational levels. The findings indicated that the pesantren successfully integrated both approaches through a unified curriculum combining traditional values and modern knowledge, innovative technology-based learning, and the strengthening of students' character through formal diniyah education and extracurricular activities. This integration model enables students to master both religious knowledge and digital skills without losing their cultural identity, preparing a generation that is morally upright, adaptive, and globally competitive. These findings served as an important reference for transforming pesantren education to remain relevant in the face of contemporary challenges.